2009
DOI: 10.1007/s10822-009-9314-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of AutoDock and PMF scoring performances, and SAR of 2-substituted pyrazolotriazolopyrimidines and 4-substituted pyrazolopyrimidines as potent xanthine oxidase inhibitors

Abstract: 4-Alkylidenehydrazino-1H-pyrazolo[3,4-d]pyrimidines, 4-arylmethylidenehydrazino-1H-pyrazolo[3,4-d]pyrimidines, and 2-substituted 7H-pyrazolo[4,3-e]-1,2,4-triazolo-[1,5-c]-pyrimidines as potential xanthine oxidase inhibitors were docked into the active site of the bovine milk xanthine dehydrogenase using two scoring functions involved in AutoDock 3.05 and the CAChe 6.1.10. The correlation coefficiency obtained between the AutoDock binding energy and IC(50) of the inhibitors was better than that obtained by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…After 100 docking runs, energy minimization was conducted to get the best structure, which also belonged to the best cluster. According to Ali et al [31], the overall docking energy of ligand molecule in its binding site is expressed as follows: Estimated G binding = intermol energy (van der Waals + hydrogen bond + electrostatic interactions + desolvation energy) + torsional energy.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…After 100 docking runs, energy minimization was conducted to get the best structure, which also belonged to the best cluster. According to Ali et al [31], the overall docking energy of ligand molecule in its binding site is expressed as follows: Estimated G binding = intermol energy (van der Waals + hydrogen bond + electrostatic interactions + desolvation energy) + torsional energy.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…Substituents on the amino group at position 4 of compound 51 resulted in very potent inhibitors of XO with hydrazone 55 being the most active in the series . SAR studies conducted on hydrazones 56 showed that the planar orientation of the pyrazolopyrimidine moiety inside the narrow channel of the enzyme active site allowed van der Waals interactions with Phe914 and Phe1009, in addition to numerous hydrogen bonds between the inhibitor and the active site of the enzyme …”
Section: Purine‐based and Purine‐like Inhibitors Of Xomentioning
confidence: 99%
“…Pyrazolo[1,5‐a]pyrimidines are also bioisosteres for triazolothienopyrimidines, imidazoquinazolines, pyrimidoquinazolines, and imidazoquinolinones, all of which have shown reported to exhibit good anticancer activity. Furthermore, pyrazolo[1,5‐a]pyrimidines have been reported to show tuberculostatic , neuroleptic , CNS depressant , antihypertensive , antileishmanial , and antimicrobial activities .…”
Section: Introductionmentioning
confidence: 99%